Pengembangan Wisata Pantai 9 Giligenting Dalam Upaya Peningkatan Perekonomian Masyarakat - Mir’Atul Fitriyah, Luluk Hanifah, (Program Studi Ekonomi Syariah Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Tarbiyatut Tholabah, 2021)
This study aims to determine (1) the profile of the nine beach destinations, Giligenting Sumenep, Madura (2) Knowing the development of coastal tourism 9 Giligenting, Sumenep, Madura and knowing the improvement of the community's economy since the existence of this tourist beach. And the choice of this location was deliberately done because Sembilan beach has been an interesting tourist destination on the island of Madura for a long time, and also its local wisdom is very interesting to visit. The research here uses the interview method through direct interviews conducted by coming directly to the location and also the documentation method that has been done. And the researchers here also made direct observations where later they had obtained data from direct interviews with the surrounding community in order to find out how the development of this Sembilan beach tourism and also the improvement of the community's economy since the existence of this Sembilan beach destination.